DESAIN SISTEM PERJALANAN DINAS BERBASIS CLOUD - Weli Weli; Medio Rahmat Gustimuda Taruna (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2020)
This study aims to analyze the process of implementing a cloud-based official travel filing system at PT. Timah Tbk. This research was conducted in January to April 2019. Analysis of system implementation was carried out based on the System Development Life Cycle method using analytical tools such as Flowcharts, Data Flow Diagrams, and Entity Relationship Diagrams. Data collection was carried out using interview and observation methods. The analysis process was carried out on the blueprint that had been made in the previous stage then continued with the implementation process using the Kec workflow application. The results of the implementation of the new system, at PT. Timah Tbk has succeeded in increasing the efficiency and effectiveness in carrying out the submission, approval, recording and realization of payment processes. In addition, the new system meets the goals the company wants, namely paperless and cashless.